2010
DOI: 10.1016/j.jcis.2009.09.038
|View full text |Cite
|
Sign up to set email alerts
|

The role of charged surfactants in the thermal and structural properties of lyotropic liquid crystalline mesophases of [Zn(H2O)6](NO3)2?CnEOm?H2O

Abstract: a b s t r a c tThe mixtures of [Zn(H 2 O) 6 ](NO 3 ) 2 salt, 10-lauryl ether (C 12 H 25 (OCH 2 CH 2 ) 10 OH, represented as C 12 EO 10 ), a charged surfactant (cetyltrimethylammonium bromide, C 16 H 33 N(CH 3 ) 3 Br, represented as CTAB or sodium dodecylsulfate, C 12 H 25 OSO 3 Na, SDS) and water form lyotropic liquid crystalline mesophases (LLCM). This assembly accommodates up to 8.0 Zn(II) ions (corresponds to about 80% w/w salt/(salt + C 12 EO 10 )) for each C 12 EO 10 in the presence of a 1.0 CTAB (or 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The surface charge of the molten phase, in the molten−surfactant interface, cannot be balanced above 70 w/w% even in the cubic mesophase. However, the addition of a charged surfactant into the media stabilizes the columnar phase up to 80 w/w% ZnX−C 12 EO 10 . Based on our observations, we believe that the salt species are in the molten phase in the hydrophilic domains of the mesophase, acting as the solvent (ionic liquid) of the media.…”
Section: Resultsmentioning
confidence: 65%
“…The surface charge of the molten phase, in the molten−surfactant interface, cannot be balanced above 70 w/w% even in the cubic mesophase. However, the addition of a charged surfactant into the media stabilizes the columnar phase up to 80 w/w% ZnX−C 12 EO 10 . Based on our observations, we believe that the salt species are in the molten phase in the hydrophilic domains of the mesophase, acting as the solvent (ionic liquid) of the media.…”
Section: Resultsmentioning
confidence: 65%
“…This is a known behavior in salt-surfactant mesophases in the presence of CTAB. 49 Our previous work showed that increasing the amount of CTAB shrinks the unit cell; however increasing the amount of salt enlarges the unit cell in the mesophase. 49 Therefore, the charged surfactant content of the mesophase determines the volume of the hydrophilic domains of the mesophase for the salt species; for samples with higher salt concentrations, the CTAB amount should be further increased to obtain a stable mesophase.…”
Section: Resultsmentioning
confidence: 95%
“…It is already known from the salt-surfactant system that increasing the salt/surfactant ratio expands the unit cell of the mesophase to accommodate more salt species. [43] Therefore, the new behaviour (no change in the unit cell) can be interpreted as a decrease in the aggregation number of the surfactant, that is, the number of surfactants per unit volume, in the mesophase to accommodate more aqueous species per surfactant. Therefore, the content of the hydrophilic domains likely does not change much with increasing aqueous species in the media.…”
Section: Resultsmentioning
confidence: 99%